PENGARUH KEADILAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA KARYAWAN - Indrayani, Luh Putu Cahya; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2016)
This study aims to determine the effect of organizational justice on job satisfaction and organizational commitment to employee Village Credit Institutions (LPD) The Village People Bualu. The population used in this study were all employees of LPD totaling 55 people, not including the leader. Method of determining the sample in this study carried out by non-probability sampling approach saturation sampling, where all populations and are not made respondents were among the leaders. The analytical tool used is the technique of path analysis (path analysis). The results obtained in this study are the organizational justice positive and significant effect on employee job satisfaction, organizational justice positive and significant impact on organizational commitment, and job satisfaction and significant positive effect on organizational commitment. This study has several limitations that this study only look that can be created through the organizational commitment factor of organizational justice and job satisfaction, but does not rule out the emergence of other factors beyond the study.
Keywords: Organizational Justice, Job Satisfaction, Organizational Commitment